Internal modes. We start by considering the case of the coefficients of internal modes, i.e.,
\(c^K_{i_1, i_2, i_3}\) as defined in (
A.49) for
\(i_n\ge 3\),
\(n=1,2, 3\). Let then
\(i_1, i_2, i_3\in \{3, \dots , p+1\}\) and write
\(L_n^k = L_n \circ \phi _k\): it follows that
$$\begin{aligned} c^K_{i_1,i_2, i_3} =&\, (2i_1-3)(2i_2-3)(2i_3-3)\nonumber \\&\int _{K} \left( {\partial _{x_1}\partial _{ x_2}\partial _{x_3}} u(x_1, x_2, x_3) \right) L_{i_1-2}^{k_1}(x_1)L_{i_2-2}^{k_2}(x_2)L_{i_3-2}^{k_3}(x_3) dx_1dx_2dx_3. \end{aligned}$$
(A.53)
If
\(u\in W_{\mathrm {mix}}^{1,1}(K)\), since
\(\Vert L_n\Vert _{L^\infty (-1,1)} = 1\) for all
n, we have
$$\begin{aligned} | c^K_{{i_1\dots i_d}} | \le (2i_1-3)(2i_2-3)(2i_3-3) \Vert \partial _{x_1}\partial _{ x_2}\partial _{x_3}u \Vert _{L^1(K)}, \qquad i_n\ge 3,\,n=1,2,3,\nonumber \\ \end{aligned}$$
(A.54)
hence,
$$\begin{aligned} \sum _{K\in {\mathcal {G}}^\ell _3}| c^K_{{i_1\dots i_d}} | \le (2i_1-3)(2i_2-3)(2i_3-3) \Vert \partial _{x_1}\partial _{ x_2}\partial _{x_3}u \Vert _{L^1(Q)}, \quad i_n\ge 3,\,n=1,2,3.\nonumber \\ \end{aligned}$$
(A.55)
Face modes. We continue with face modes and fix, for ease of notation,
\(i_1 =1\). We also denote
\(F = J^\ell _{k_2}\times J^\ell _{k_3}\). The estimates will then also hold for
\(i_1=2\) and for any permutation of the indices by symmetry. We introduce the trace inequality constant
\(C^{T,1}\), independent of
K, such that, for all
\(v\in W^{1,1}(Q)\) and
\({\hat{x}}\in (0,1)\),
$$\begin{aligned} \Vert v({\hat{x}}, \cdot , \cdot ) \Vert _{L^1(F)} \le \Vert v({\hat{x}}, \cdot , \cdot )\Vert _{L^1((0,1)^2)} \le C^{T,1} \left( \Vert v\Vert _{L^1(Q)} + \Vert \partial _{x_1} v \Vert _{L^1(Q)} \right) .\nonumber \\ \end{aligned}$$
(A.56)
This follows from the trace estimate in [
49, Lemma 4.2] and from the fact that
$$\begin{aligned} \Vert v({\hat{x}}, \cdot , \cdot )\Vert _{L^1((0,1)^2)}&\le C\min \bigg \{ \frac{1}{|1-{\hat{x}}|}\Vert v\Vert _{L^1(({\hat{x}},1)\times (0,1)^2)} + \Vert \partial _{x_1} v \Vert _{L^1(({\hat{x}}, 1)\times (0,1)^2)},\\&\quad \frac{1}{|{\hat{x}}|}\Vert v\Vert _{L^1((0,{\hat{x}})\times (0,1)^2)} + \Vert \partial _{x_1} v \Vert _{L^1((0,{\hat{x}})\times (0,1)^2)} \bigg \}. \end{aligned}$$
For
\(i_2, i_3\in \{3, \dots , p+1\}\),
$$\begin{aligned} c^K_{1,i_2, i_3} = (2i_2-3)(2i_3-3)\int _{F} \left( {\partial _{ x_2}\partial _{x_3}} u(x_{k_1+1}^{\ell }, x_2, x_3) \right) L_{i_2-2}^{k_2}(x_2)L_{i_3-2}^{k_3}(x_3) dx_2dx_3.\nonumber \\ \end{aligned}$$
(A.57)
Since the Legendre polynomials are
\(L^\infty \)-normalized and using the trace inequality (
A.56),
$$\begin{aligned} |c_{1, i_2, i_3}^K|\le & {} (2i_2-3)(2i_3-3) \Vert ({\partial _{ x_2}\partial _{x_3}} u )(x_{k_1+1}^{\ell }, \cdot , \cdot )\Vert _{L^1(F)} \nonumber \\\le & {} C^{T,1}(2i_2-3)(2i_3-3) \Vert u \Vert _{W_{\mathrm {mix}}^{1,1}(Q)}. \end{aligned}$$
(A.58)
Summing over all internal faces, furthermore,
$$\begin{aligned} \begin{aligned} \sum _{K\in {\mathcal {G}}^\ell _3}|c_{1, i_2, i_3}^K|&\le (2i_2-3)(2i_3-3) \sum _{k_1=0}^\ell \Vert ({\partial _{ x_2}\partial _{x_3}} u )(x_{k_1+1}^{\ell }, \cdot , \cdot )\Vert _{L^1((0,1)^2)}\\&\le C^{T,1}(\ell +1)(2i_2-3)(2i_3-3) \Vert u \Vert _{W_{\mathrm {mix}}^{1,1}(Q)}. \end{aligned} \end{aligned}$$
(A.59)
Edge modes. We now consider edge modes. Fix for ease of notation
\(i_1 = i_2 = 1\); as before, the estimates will hold for
\((i_1, i_2)\in \{1,2\}^2\) and for any permutation of the indices. By the same arguments as for (
A.56), there exists a trace constant
\(C^{T,2}\) such that, denoting
\(e = J^\ell _{k_3}\), for all
\(v\in W^{1,1}((0,1)^2)\) and for all
\({\hat{x}}\in (0,1)\),
$$\begin{aligned} \Vert v ({\hat{x}}, \cdot )\Vert _{L^1(e)} \le \Vert v ({\hat{x}}, \cdot )\Vert _{L^1((0,1))} \le C^{T,2} \left( \Vert u\Vert _{L^1((0,1)^2)} + \Vert \partial _{x_1} u \Vert _{L^1((0,1)^2)} \right) .\nonumber \\ \end{aligned}$$
(A.60)
By definition,
$$\begin{aligned} c^K_{1,1, i_3} = (2i_3-3)\int _{e} \left( {\partial _{x_3}} u(x_{k_1+1}^{\ell }, x_{k_2+1}^{\ell }, x_3) \right) L_{i_3-2}^{k_3}(x_3) dx_3. \end{aligned}$$
(A.61)
Using (
A.56) and (
A.60)
$$\begin{aligned} |c^K_{1,1, i_3} |\le & {} (2i_3-3) \Vert (\partial _{x_3} u)(x_{k_1+1}^{\ell }, x_{k_2+1}^{\ell }, \cdot ) \Vert _{L^1(e)} \nonumber \\\le & {} C^{T,1} C^{T,2}(2i_3-3) \Vert u\Vert _{W_{\mathrm {mix}}^{1,1}(Q)}. \end{aligned}$$
(A.62)
Summing over edges, in addition,
$$\begin{aligned} \begin{aligned} \sum _{K\in {\mathcal {G}}^\ell _3}|c^K_{1,1, i_3} |&\le (2i_3-3) \sum _{k_1=0}^\ell \sum _{k_2=0}^\ell \Vert (\partial _{x_3} u)(x_{k_1+1}^{\ell }, x_{k_2+1}^{\ell }, \cdot ) \Vert _{L^1((0,1))}\\&\le C^{T,1} C^{T,2}(\ell +1)^2(2i_3-3) \Vert u\Vert _{W_{\mathrm {mix}}^{1,1}(Q)}. \end{aligned} \end{aligned}$$
(A.63)
Node modes. Finally, we consider the coefficients of nodal modes, i.e.,
\(c^K_{i_1, i_2, i_3}\) for
\(i_1, i_2, i_3\in \{1,2\}\), which by construction equal function values of
u, e.g.,
$$\begin{aligned} c_{111} = u(x_{k_1+1}^{\ell },x_{k_2+1}^{\ell },x_{k_3+1}^{\ell }). \end{aligned}$$
(A.64)
The Sobolev imbedding
\(W_{\mathrm {mix}}^{1,1}(Q)\hookrightarrow L^{\infty }(Q)\) and scaling implies the existence of a uniform constant
\(C_{\mathrm {imb}}\) such that, for any
\(v\in W_{\mathrm {mix}}^{1,1}(Q)\)$$\begin{aligned} \Vert v \Vert _{L^\infty (K)} \le \Vert v \Vert _{L^\infty (Q)} \le C_{\mathrm {imb}} \Vert v \Vert _{W_{\mathrm {mix}}^{1,1}(Q)}. \end{aligned}$$
Then, by construction,
$$\begin{aligned} |c^K_{i_1, i_2, i_3}| \le \Vert u \Vert _{L^\infty (K)} \le C_{\mathrm {imb}} \Vert u \Vert _{W_{\mathrm {mix}}^{1,1}(Q)}, \qquad \forall i_1, i_2, i_3\in \{1,2\}. \end{aligned}$$
(A.65)
Summing over nodes, it follows directly that
$$\begin{aligned} \sum _{{K\in {\mathcal {G}}^\ell _3}}|c^K_{i_1, i_2, i_3}| \le \sum _{K\in {\mathcal {G}}^\ell _3}\Vert u \Vert _{L^\infty (K)} \le C_{\mathrm {imb}} (\ell +1)^3\Vert u \Vert _{W_{\mathrm {mix}}^{1,1}(Q)}, \quad \forall i_1, i_2, i_3\in \{1,2\}.\nonumber \\ \end{aligned}$$
(A.66)
We obtain (
A.51) from (
A.54), (
A.58), (
A.62), and (
A.65). Furthermore, (
A.52) follows from (
A.55), (
A.59), (
A.63), and (
A.66). The estimates for the case
\(d=2\) follow from the same argument.
\(\square \)